A Sunscreen‐Based Photocage for Carbonyl Groups. Issue 32 (28th April 2020) - Lineros‐Rosa, Mauricio; Miranda, Miguel A.; Lhiaubet‐Vallet, Virginie
Abstract: Photolabile protecting groups (PPGs) have been exploited in a wide range of chemical and biological applications, due to their ability to provide spatial and temporal control over light‐triggered activation. In this work, we explore the concept of a new photocage compound based on the commercial UVA/UVB filter oxybenzone (OB; 2‐hydroxy‐4‐methoxybenzophenone) for photoprotection and controlled release of carbonyl groups. The point here is that oxybenzone not only acts as a mere PPG, but also provides, once released, UV photoprotection to the carbonyl derivative. This design points to a possible therapeutic approach to reduce the severe photoadverse effects of drugs containing a carbonyl chromophore. Abstract : Carbonyl photoprotection : The design of a new photocage achieves two main goals: an extension of the organic chemist's toolbox, providing a new carbonyl photoprotecting group, and a proof of concept for sunscreen‐based photocages for carbonyl‐derived drugs, allowing the controlled and simultaneous photorelease of a photosensitive drug and its protecting solar filter (see scheme).